Ecosystem dynamics under top-down and bottom-up control situations generated by intensive harvesting rates - Arreguín-Sánchez, Francisco (HIDROBIOLÓGICA, 2017)
Top-down and bottom-up control processes in exploited ecosystems have been characterised using their impacts on the mean trophic level of catches, changes in biomass, and certain ecosystem attributes. Most scientific contributions have been based on case studies of particular ecosystems. So, the aim of this study is to identify and understand ecosystem processes governing their response to fishing in a more global sense. Simulations were developed using different ecosystems models using the Ecopath with Ecosim suite of programs. Two cases were examined by selecting target species to be exploited during simulations experiments. A high trophic level group (sharks) and a low trophic level group (shrimp) were chosen to represent potential top-down and bottom-up control situations, respectively. For both cases, a gradient of exploitation was simulated, and ecosystem attributes were estimated. Harvest rates (HR) varied along a gradient of HR = 0.4 to HR = 0.7 for sharks and HR = 0.3 to HR = 0.8 for shrimp. For each simulation, only the target group was modified. Principal Components Analysis was applied, and outputs were obtained using ecosystems as variables and attributes as factors, and vice versa. For sharks, outputs indicate that under a low HR, group attributes govern the response to exploitation. However, when a high HR was applied (higher than the maximum sustainable yield), ecosystem attributes emerged as relevant instead of stock attributes. For sharks, representing top-down control, a graphical arrangement of the first two components clearly shows a gradual pattern of response reflecting the transition from stock-level to ecosystem-level processes as HR increases. For shrimp, representing bottom-up control, no clear patterns emerged; in this case, the same relevant stock and ecosystem attributes appear across all HRs applied. These results are explained in terms of stock life histories, trophic level, and transfer efficiencies through the food web, suggesting that ecosystem processes behind overfishing are related to the trophic level, and then, fisheries management practice must recognise such particularities.